Possibility of producing plastic lubricants by thermal destruction of solid domestic wastes - Grigorov, Andrey; Zelenskii, Oleg; Sytnik, Alexey; Nahliuk, Ivan (My University, 2020)
The results of non-catalytic thermal destructive processing of solid domestic waste at atmospheric pressure and temperature of 360°C, which are represented by products of low pressure polyethylene, are presented. The products obtained during degradation can be divided into fuel products (gas, liquid hydrocarbon fraction, coke residue) and fraction (with the beginning of boiling in the temperature range 200-320°C), which can be used in the production of greases. After the heat treatment and cooling of these fractions, a product with properties similar to NYCO 65 VASELINE (Technical petrolatum (GREASE)) can be obtained. For the production of plastic lubricants with other properties and a large temperature interval of application, a scheme has been proposed, it provides for the addition of fillers and additives of different functional purpose to the lubricant obtained.
Keywords: thermal destruction; plastic lubricant; dispersion medium; polyethylene products; quality indicators